Predisposing, enabling, and need factors associated with utilization of HCV testing services among PWID in two settings in India. Issue 1 (December 2016) - Sogarwal, Ruchi; Madge, Varada; Bishi, Pratyush; Woleng, Apam; Garg, Rishi
Abstract Background The Hepatitis C virus (HCV) is very common among people who inject drugs (PWID), yet PWID in India have suboptimal access to HCV testing and treatment. This study sought to identify HCV risk factors among male PWID who utilized a free needle and syringe exchange program and to examine the predisposing, enabling, and need factors associated with utilization of HCV testing services by those PWID reporting that they had been tested. Methods A cross-sectional study was conducted in Imphal, Manipur and Amritsar, Punjab. These two settings have high HCV prevalence and large numbers of PWID. A team of 18 field investigators obtained data through face-to-face interviews using a structured multiple-choice questionnaire. The questionnaire was administered to 1241 of 2644 male PWID aged 15 years and above enrolled in the needle and syringe program of India's AIDS Control Program, with study participants selected through consecutive sampling. Statistical analyses included descriptive statistics and multivariate regression. Results Twenty-four percent of PWID in our study sample reported having been tested for HCV. Unlike PWID in Imphal, more than half of PWID in Amritsar reported unprotected sex and use of alcohol or non-injecting drugs as being among their HCV risk factors (67.1 and 77.8 %, respectively). However, opioid substitution therapy non-adherence was reported more often in Imphal than in Amritsar. Education, marital status, place of residence and duration of injecting drug use were found to significantly enable access to HCV testing while alcohol use, frequent mobility and unprotected sex were found to significantly inhibit access to HCV testing for PWID after controlling for other explanatory variables. Conclusions Predisposing and enabling determinants provide an area for developing effective interventions to improve HCV testing practices among PWID. HCV prevention programs that address safe injecting and sexual practices, OST adherence and frequent mobility customized for PWID by age are strongly recommended.